Sweden's Business Climate : Opportunities for Entrepreneurs through Improved Regulations - World Bank Group (World Bank, Washington, DC, 2015)
This report’s starting point is thus to acknowledge that despite Sweden’s many virtues, there are areas in which it can do better, and the task has been to identify those areas, focusing particularly on the quality of the investment climate and competitiveness. This has been done in two main ways. First, by looking at areas of the business environment captured by databases compiled in the World Bank Group’s Global Indicators Group—Doing Business, Foreign Direct Investment (FDI) Regulations, and Women, Business and the Law. And second, by examining other critical areas where there is a large body of data, knowledge and insight that casts relevant light on several key policy challenges facing the country in coming years. In the paragraphs that follow we present a summary of the report’s main conclusions.